Research on chemical control of peach shoot blight and the association between phloem volatile compounds and resistance - HU Zhu; WANG Li; ZHAO Hongyue (Guoshu xuebao)
[Objective] Prunus persica (L.) Batsch, a member of the Rosaceae family, is native to China and has a cultivation and evolutionary history spanning thousands of years. In recent years, peach shoot blight caused by Diaporthe amygdali has been one of the most prevalent fungal diseases in major peachproducing regions of southern China. This study aimed to screen out highly effective chemical fungicides for controlling peach shoot blight, and investigated the relationship between volatile compounds in the phloem of peach shoots and resistance to the disease, providing a scientific basis for integrated disease management strategies and resistance breeding programs. [Methods] The inhibitory effects of 15 fungicides against D. amygdali were evaluated in vitro using the mycelial growth rate method. The active ingredient information was as follows: difenoconazole, pyraclostrobin, propiconazole, boscalid, carbendazim, hymexazol, flusilazole, fludioxonil, hexaconazole, prochloraz, azoxystrobin, trifloxystrobin, tebuconazole, lprodione, and dithianon. A series of concentrations were prepared for each fungicide. The effective medium concentration (EC50) values were calculated based on the correlation between fungicide concentration and mycelial growth inhibition rate by DPS in this study. At the same time, healthy and disease-free one-year-old shoot phloem tissues were collected from 22 peach varieties, which exhibited varying levels of resistance to D. amygdali. After rapid freezing within the liquid nitrogen, the samples were transported to the laboratory for volatile compound analysis. Volatile compounds were extracted and analyzed using Headspace Solid-Phase Microextraction coupled with Gas Chromatography-Mass Spectrometry (HS-SPME-GC-MS). The correlation between the relative content of each identified volatile compound and the resistance level of the corresponding variety was examined. In addition, two typical peach cultivars (Fenghua Pantao, susceptible; and Hakuho, highly susceptible) were selected for inoculation with D. amygdali. Phloem tissue around necrotic spots was collected 7 days after inoculation, flash-frozen, and used for volatile compound analysis. Key volatile compounds significantly correlated with resistance (identified in the correlation analysis) were quantified in these tissues to observe pathogen-induced changes. [Results] The toxicity test of fungicides showed that prochloraz had the strongest inhibitory effect, with an EC50 value of 0.004 2 mg·L-1. Difenoconazole, pyraclostrobin, propiconazole, fludioxonil, flusilazole, hexaconazole, and tebuconazole also showed strong activity. Boscalid showed the weakest inhibitory effect, with an EC50 value of 49.025 2 mg·L-1. Analysis of volatile compounds content showed that volatile compounds were identified in 22 peach samples. A total of 121 volatile compounds were identified, falling into 12 distinct categories: 30 terpenoids, 22 esters, 17 alcohols, 16 ketones, 13 aldehydes, 5 alkanes, 4 fatty acids, 3 phenolics, 3 furans, 2 acids, 1 lactone, and 5 other compounds. Among the samples, Richuan Baifeng and Reddomun had the highest number of volatile compounds, with 85 and 80, respectively. In contrast, the samples Baihua and Zhouxingshantao had the fewest, with 52 and 51 compounds, respectively. To identify volatile metabolites associated with resistance to D. amygdali, we conducted a correlation analysis between the volatile substance content and germplasm resistance to D. amygdali across 22 samples. Sixteen compounds were significantly and negatively correlated with resistance, and six were significantly and positively correlated. Negatively correlated compounds included one acid, one aldehyde, two alkanes, two esters, one fatty acid, four ketones, one phenolic compound, and four terpenoids. The ester compound icosyl oleate had the strongest negative correlation, with a coefficient of-0.676 5 (P<0.01). Positively correlated compounds included one alcohol, two aldehydes, one ester, one ketone, and one terpenoid. Among these, the aldehyde 2-heptenal had the highest positive correlation, with a coefficient of 0.570 4 (P<0.01). The distribution of two volatile compounds (a: n-Hexadecane; b: 1-Nonanol) with different resistance level to D. amygdali of 22 peach varieties was revealed. To further validate the relationship between volatile compounds and shoot blight resistance, we selected two peach cultivars with different resistance levels and inoculated them with D. amygdali. After 7 days, lesion diameters reached 52.62 mm in Fenghua Pantao and 84.50 mm in Hakuho. Volatile compounds in the phloem tissue around the lesions were analyzed in both samples. After inoculation, the content of the volatile compound 2-heptenal, positively correlated with resistance, rapidly increased in the susceptible germplasm Fenghua Pantao, in comparison to the highly susceptible germplasm Hakuho, suggesting that higher 2-heptenal levels may enhance resistance. Benzoic acid, negatively correlated with resistance, was induced in both germplasms, but the increase was smaller in susceptible peaches, suggesting that lower accumulation may reduce resistance. [Conclusion] Among the 15 fungicides, prochloraz exhibited the strongest inhibitory effect, with an effective medium concentration value of 0.004 2 mg·L-1. Correlation analysis identified 16 compounds that were significantly and negatively correlated with resistance, with the ester icosyl oleate showing the strongest correlation (r=-0.676 5). Six compounds were significantly and positively correlated, with 2-heptenal showing the highest correlation (r=0.570 4). This study layed an important theoretical foundation for achieving sustainable comprehensive control of peach shoot blight.